(untitled) (Research, Society and Development, 2020)
At the end of 2019, the new coronavirus 2019 emerged in Wuhan, China, being responsible for the COVID-19 disease, which causes several clinical conditions ranging from mild nonspecific symptoms to severe pneumonia with damage to organic function. Taking into consideration that a balanced diet can significantly help patients in the control of chronic infectious diseases, the aim of this study was to discuss and present recent data regarding the role of vitamins A, C, D, and E, and the minerals zinc and selenium in the treatment of COVID-19. This is a narrative review concerning the aspects of the COVID-19 pandemic and data related to vitamins and minerals, as well as its nutritional importance for the treatment of the disease. The alterations caused by the deficiency of plasma concentrations of vitamins and minerals involve the reduction of the good performance of the immune system, which is one of the factors that lead to a deficient immune state. However, further studies are needed to elucidate the relationship between micronutrients and infection caused by COVID-19.